Pemanfaatan Media Kartu Kata Bergambar dalam Meningkatkan Kemampuan Membaca dan Kognitif pada Anak Usia Dini di RA Al Jannah Jakarta Utara - Juwariah, Siti; Susanto, Susanto; Sastradiharja, EE Junaedi (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the use of picture word card media which is carried out with several methods or ways of recognizing vocabulary in each theme in improving early childhood reading and cognitive skills in RA Al Jannah. This study uses a qualitative approach with literature study methods and in-depth interviews. The instruments used are interview and observation sheets as well as several studies that examine the theme. The data produced are primary and secondary data. The data analysis carried out was to review the literature and triangulation of data based on the results of interviews and observations. The introduction of word cards is carried out every day consistently and repeatedly, picture word cards are also used in the form of games and also singing, there are several models of word cards used in RA Al Jannah, namely theme word cards, harmony word cards, fishing word cards, bingo word cards, and reminder card cards. The strategy for improving early childhood reading skills carried out with the media of picture word cards is in a gradual way, namely through a phonetic approach, syllable recognition, whole language, interactive and fun activities. Cognitive improvement strategies carried out in Ra various games, namely by means of word grouping games and memory games, examples of memory games carried out are games with reminder word cards, bingo word cards, picture guessing games, and fishing games with syllables.